The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3748/wjg.v25.i19.2327
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for progression to acute-on-chronic liver failure during severe acute exacerbation of chronic hepatitis B virus infection

Abstract: BACKGROUND Acute exacerbation in patients with chronic hepatitis B virus (HBV) infection results in different severities of liver injury. The risk factors related to progression to hepatic decompensation (HD) and acute-on-chronic liver failure (ACLF) in patients with severe acute exacerbation (SAE) of chronic HBV infection remain unknown. AIM To identify risk factors related to progression to HD and ACLF in compensated patients with SAE of chronic HBV infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
1
13
1
Order By: Relevance
“…These findings help to explain the positive correlations between 3-month prognosis and TBil, PT-INR, infection, HE, as well as PALS model and its simplified PALS score. Although contradictory results between the presence of LC and the progress or prognosis of ACLF have been reported previously 36 38 , our study do find that the presence of LC is an independent prognostic risk factor for patients with ACLF along with other studies 39 41 . However, the possible negative correlation between age and prognosis was not found in our study even though age was reported to be an independent risk factor in predicting development of ACLF 36 , 38 , and decreased capacity of liver regeneration and impaired immune function were reported in older patients 42 , 43 .…”
Section: Discussioncontrasting
confidence: 75%
“…These findings help to explain the positive correlations between 3-month prognosis and TBil, PT-INR, infection, HE, as well as PALS model and its simplified PALS score. Although contradictory results between the presence of LC and the progress or prognosis of ACLF have been reported previously 36 38 , our study do find that the presence of LC is an independent prognostic risk factor for patients with ACLF along with other studies 39 41 . However, the possible negative correlation between age and prognosis was not found in our study even though age was reported to be an independent risk factor in predicting development of ACLF 36 , 38 , and decreased capacity of liver regeneration and impaired immune function were reported in older patients 42 , 43 .…”
Section: Discussioncontrasting
confidence: 75%
“…Among these scoring systems, only MELDs has been evaluated to predict the progression to HBV-related ACLF. Although high MELDs was associated with progression to ACLF, the predictive value of MELDs was not satisfying with the AUROC ranged from 0.601 to 0.820 [1][2][3]9]. There are currently a few specifically designed predictive models for the progression of HBV-related ACLF superior to MELDs.…”
Section: Non-invasive Tools To Predict Hbv-related Aclfmentioning
confidence: 97%
“…The sum risk score ranged from 0 to 7, and 4-7 identified patients with higher risk of ACLF (26.0%-68.8%). Another two prediction models established by Li et al [1] (containing age, PTA, TBIL, bilirubin, Na and HBV DNA) and Yuan et al [2] (containing age and HBV DNA) could predict HBV-related ACLF more effectively than MELDs.…”
Section: Non-invasive Tools To Predict Hbv-related Aclfmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictors were collected using an online electronic case report form, and their integrity was systematically checked before being entered into the model. We selected the predictors from the electronic health records based on published literature (27)(28)(29) and our clinical experience. Baseline data were the data obtained at the first diagnosis of SAE of CHB from the computerized and paper medical records.…”
Section: Predictorsmentioning
confidence: 99%